2017
DOI: 10.5551/jat.39545
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C–Adiponectin Complex in Plasma Associates with Coronary Plaque Instability

Abstract: Aim: Adiponectin (APN) is an adipocyte-derived bioactive molecule with antiatherogenic properties. We previously reported that cystatin C (CysC) abolished the anti-atherogenic effects of APN. We aimed to elucidate the clinical significance of CysC–APN complex in patients with coronary artery disease (CAD).Methods: We enrolled 43 stable CAD male patients to examine the relationship between CysC–APN complex and coronary plaque characteristics. Serum was immunoprecipitated by the anti-APN antibody and immunoblott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Angiography cannot visualize plaques and shows only the severity and morphology of stenotic lesions. However, in our study, intravascular ultrasound (IVUS) or optical coherence tomography (OCT), which can visualize coronary plaques and evaluate plaque characteristics 32 ) , were not always performed. Second, we did not measure blood legumain levels in the coronary sinus.…”
Section: Discussionmentioning
confidence: 91%
“…Angiography cannot visualize plaques and shows only the severity and morphology of stenotic lesions. However, in our study, intravascular ultrasound (IVUS) or optical coherence tomography (OCT), which can visualize coronary plaques and evaluate plaque characteristics 32 ) , were not always performed. Second, we did not measure blood legumain levels in the coronary sinus.…”
Section: Discussionmentioning
confidence: 91%
“…44 Of the remaining biomarkers identified by regression network analysis at high stringency, the adiponectincystatin C cluster was notable, particularly in view of the recent finding that these proteins are complexed in plasma. 45 The finding that cystatin C is an inhibitor of adiponectin-mediated vasculoprotective effects suggests that the marked increment in adiponectin levels seen on niacin (72%), and thus its potential biological actions, were largely neutralized by complexation with cystatin C. 45 This effect is of considerable relevance to the potential attenuating impact of niacin on the pathophysiology of cardiometabolic disease, as adiponectin is an insulin sensitizer, modulates inflammatory responses, and promotes macrophage polarization to the antiinflammatory M2 phenotype. 46 Indeed, the induction of insulin resistance by ER niacin in this MetS cohort was not attenuated by major increment in adiponectin (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, AdipoR1 and AdipoR2, the cell membrane-bound receptors of APN, are involved in insulin sensitivity and antidiabetic effects, whereas calreticulin promotes the removal of apoptotic cells via binding to APN. We have reported several APN-associating molecules, ESL-1 22) , CysC 23) , and…”
Section: Systemmentioning
confidence: 99%
“…Recently, we determined several APN-interacting molecules, E-selectin ligand-1 (ESL-1) 22) , cystatin C (CysC) 23) , and Mac-2 binding protein (M2BP) 24) , and we demonstrated that the functions of APN and its interacting molecules are mutually regulated. Moreover, the possible interaction between APN and several chemokines was suggested in a previous report 25) .…”
Section: Introductionmentioning
confidence: 99%